2005
DOI: 10.2308/jiar.2005.4.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Voluntary Disclosure of Pro Forma Earnings: A U.S.-Canada Comparison

Abstract: This study compares managers' voluntary disclosure of pro forma earnings—an alternative measure to generally accepted accounting principals (GAAP) earnings—in the U.S. and Canada. The results indicate some distinct differences between the two countries in that U.S. managers (1) disclose pro forma earnings more frequently, (2) place greater emphasis on the pro forma earnings number relative to the GAAP earnings figure, and (3) make greater (income-increasing) adjustments from GAAP in calculating pro forma earni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Although evidence is found for the strategic use of alternative performance measures (e.g. Doyle and Soliman, 2002;Bhattacharya et al, 2004;Lougee and Marquardt, 2004;Bowen et al, 2005;Entwistle et al, 2005;Black and Christensen, 2009;Doyle et al, 2013), results suggest that reported alternative performance measures are relevant for investor decisionmaking (e.g. Bhattacharya et al, 2003;Brown and Sivakumar, 2003;Lougee and Marquardt, 2004) and provide incremental information beyond the net income number alone.…”
Section: Other Disaggregations Of Earningsmentioning
confidence: 90%
“…Although evidence is found for the strategic use of alternative performance measures (e.g. Doyle and Soliman, 2002;Bhattacharya et al, 2004;Lougee and Marquardt, 2004;Bowen et al, 2005;Entwistle et al, 2005;Black and Christensen, 2009;Doyle et al, 2013), results suggest that reported alternative performance measures are relevant for investor decisionmaking (e.g. Bhattacharya et al, 2003;Brown and Sivakumar, 2003;Lougee and Marquardt, 2004) and provide incremental information beyond the net income number alone.…”
Section: Other Disaggregations Of Earningsmentioning
confidence: 90%
“…Common components of non-GAAP adjustments Bhattacharya, Black, Christensen, and Larson (2003), Bhattacharya, Black, Christensen, and Mergenthaler (2004), Bowen, Davis, and Matsumoto (2005), and Entwistle, Feltham, and Mbagwu (2005) identified categories of adjustments from GAAP earnings to derive non-GAAP earnings information. These studies used data from periods prior to the implementation of Reg.…”
Section: Use Of Non-gaap Measuresmentioning
confidence: 99%
“…Three of the categories were used four times in prior studies: depreciation and amortization costs, stock based compensation, and restructuring charges. Bhattacharya et al (2004), Entwistle et al (2005), and Elliott (2006) identified common adjustments to GAAP earnings used by US companies prior to the enactment of Reg. G. Bowen et al (2005) examined the emphasis placed on non-GAAP measures in pre-Reg.…”
Section: Use Of Non-gaap Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing research, the majority of which is empirical, has examined these two competing disclosure motives for reporting pro forma earnings: to manage investor's perceptions (i.e., to potentially mislead), or to provide value relevant information. Studies reporting evidence consistent with the first motive include Bowen et al (2004), Doyle and Soliman (2002), Entwistle et al (2005), and Lougee and Marquardt (2004). Research supporting pro forma earnings having value relevance includes Bhattacharya et al (2003), Bradshaw and Sloan (2002), Brown and Sivikumar (2003), and Entwistle et al (2004).…”
Section: Background Information and Relevant Literaturementioning
confidence: 99%